Design of load frequency control for power systems with BESS and generation rate constraint subject to persistent load disturbances - Arunsawatwong, Suchin; Kalvibool, Patipan (TENCON ... IEEE Region Ten Conference, 2016)
The waveforms of electric power generated from renewable energy sources can vary persistently in a random manner for a long period of time. This paper presents the design of load frequency controllers for power systems that are subject to persistent disturbances by using the principle of matching and the method of inequalities. In the design formulation, the generation rate constraint is explicitly taken into account and a battery energy storage system (BESS) is used. Moreover, a PI controller in the main loop and a lag/lead controller in the BESS minor loop are designed simultaneously so as to mitigate the effects of power fluctuation caused by normal load and renewable energy sources. The principal design objective is to guarantee that the peak magnitudes of frequency deviation, generation rate and BESS power output always stay strictly within respective bounds despite all possible disturbances. The numerical results clearly show that the framework adopted here is suitable for solving such a design problem.